2003
DOI: 10.1016/s0167-8809(02)00225-6
|View full text |Cite
|
Sign up to set email alerts
|

Participatory conservation tillage research: an experience with minimum tillage on an Ethiopian highland Vertisol

Abstract: 10Farmer participatory tillage trials were conducted in a highland Vertisol area of Ethiopia during the 1999 and 2000 cropping seasons. This participatory initiative clearly demonstrated that incorporating farmers' knowledge, ideas and preferences could improve the wheat production package. A traditional practice of Chefe Donsa farmers-applying ash from their homesteads to their fields to enable early-sown crops to withstand frost-led to the verification of the yield-enhancing effect of inorganic potassium fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The % FNUE values reported for the Nitosol are adequate (above 50%). Vertisols are generally regarded as problematic soils in Ethiopia due to their distinctive hydro-physical properties, which lead to a high incidence of prolonged water-logging and limitation of nutrient availability and plant growth (Asgelil et al 2001;Syers et al 2001;Astatke et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The % FNUE values reported for the Nitosol are adequate (above 50%). Vertisols are generally regarded as problematic soils in Ethiopia due to their distinctive hydro-physical properties, which lead to a high incidence of prolonged water-logging and limitation of nutrient availability and plant growth (Asgelil et al 2001;Syers et al 2001;Astatke et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Extensive research has been conducted into the broader frameworks of integrated soil fertility management [130][131][132][133][134][135][136][137], conservation agriculture [138][139][140][141][142][143], erosion control [144][145][146][147][148], and improved grazing management [149][150][151]. There is also a wealth of information on the benefits of specific practices such as short legume rotations (improved fallows) [152][153][154][155][156][157][158], agroforestry systems [159][160][161][162][163][164][165], and no-till systems [166][167][168][169][170].…”
Section: Positive Trajectories and Conclusionmentioning
confidence: 99%
“…Reduced cost of production, such as reduced labour, fuel and machinery, is a key advantage of reduced tillage practices (Fowler and Rockstrom, 2001) and is reported to result in more net benefits in reduced than in conventional tillage (Knowler and Bradshaw, 2006). For example, Astatke et al (2003) found a higher gross margin of US$132 per hectare for wheat production in reduced than in conventional tillage in Ethiopia. In another study carried out over a 16-year period in Spain, no significant differences in gross margins between reduced and conventional tillage were found, although the margins tended to be higher for the former than for the latter tillage practice (Sánchez-Girón et al, 2004).…”
Section: Economic Analysesmentioning
confidence: 99%